Effects of Medicaid expansion on insurance coverage and health services use among adults with disabilities newly eligible for Medicaid. (26th July 2022) - Creedon, Timothy B.; Zuvekas, Samuel H.; Hill, Steven C.; Ali, Mir M.; McClellan, Chandler; Dey, Judith G.
Abstract: Objective: To estimate the effects of Affordable Care Act (ACA) Medicaid expansion on insurance and health services use for adults with disabilities who were newly eligible for Medicaid. Data Sources: 2008–2018 Medical Expenditure Panel Survey data. Study Design: We used the Agency for Healthcare Research and Quality (AHRQ) PUBSIM model to identify adults aged 26–64 years with disabilities who were newly Medicaid‐eligible in expansion states or would have been eligible in non‐expansion states had those states opted to expand. Outcomes included insurance coverage; access to care; receipt of primary care, outpatient specialty physician services, and preventive services; and out‐of‐pocket health care spending. To estimate the effects of Medicaid expansion, we used two‐way fixed effects models and a triple differences framework to compare pre‐post changes in each outcome in expansion and non‐expansion states for adults with and without disabilities. Extraction Methods: We simulated Medicaid eligibility with the AHRQ PUBSIM model, which uses state‐specific Medicaid rules and MEPS data on family relationships, state of residence, and income. Principal Findings: Among adults with disabilities who were newly eligible for Medicaid, Medicaid expansion was associated with significant increases in full‐year Medicaid coverage (35.9 percentage points [pp], p  < 0.001), receipt of primary care (15.5 pp, p  < 0.01), and receipt of flu shots (19.2 pp, p  < 0.01), and a significant decrease in out‐of‐pocket spending (−$457, p  < 0.01). There were larger improvements for adults with disabilities compared to those without disabilities in full‐year Medicaid coverage (11.0 pp, p  < 0.01) and receipt of flu shots (18.0 pp, p  < 0.05). Conclusions: Medicaid expansion was associated with improvements in full‐year insurance coverage, receipt of primary and preventive care, and out‐of‐pocket spending for adults with disabilities who were newly eligible for Medicaid. For insurance coverage, preventive care, and some primary care measures, there were differentially larger improvements for adults with disabilities than for those without disabilities.